Modelagem e análise estrutural de ligações de base de colunas estruturais em perfis de aço - Ramos, Heitor Rodrigues (Brasil, 2023)
There is a growing trend in the construction of steel structures, driven by the quick and clean application on-site, versatility, among other advantages. The proper functioning of a steel structure, with good parameters of stability, safety, economy, and efficiency, depends directly on how the connections were considered. Both rigid and flexible connections have their advantages and disadvantages, and the choice between these two types depends on various factors. The present study aimed to evaluate the modeling aspects of two models of base connections for steel columns using AutoDesk Revit® 2022 and IDEA StatiCa® 2023 software, analyzing the stiffness values obtained through numerical analysis and the influence of varying the base plate thickness on the connection's stiffness. Furthermore, the interoperability between the computational modeling software and the structural analysis software was assessed, verifying the implications of connection modeling in steel structure projects. The results demonstrate that only the arrangement of anchor bolts on the base plate, in some cases, may not determine the classification of the connection in terms of its stiffness. The base plate thickness has shown to influence the stiffness values for the studied connection typology. The used software tools provide features that can significantly assist in modeling, with efficient information flow and more accurate structural analysis using the finite element method.